MODEL PEMBELAJARAN THINK TALK WRITE BERBANTU KARTU MISTERIUS PADA PEMBELAJARAN SISWA KELAS IV SD NEGERI BATURSARI 6 - Mya Setyawinarsih, Ryky Mandar Sary (MALIH PEDDAS, 2014)
This research based on the strategies problem to the process of learning that is not appropriate to the requirement of the curriculum 2013 and the lack of the studentsâ learning result. The purpose of the research to know the effect of learning model Think Talk Write assisted mysterious card towards learning with the theme of my hero at the fourth grade students of SD Batursari 6. The type of this research is True Experimental Design within posttest only control design. The sample of the research is 76 students that is chosen by using sampling purposive technic. The data in this research is obtained from the average of attitude value, skill and knowledge. The result of data analysis show that the percentage of study completion improvement is 81,57 % and the percentage of learning result increase 11,53 %. The coefficient of thitung = 3,063 and ttabel with the significance level 5% = 2,021, so thitung > ttabel and H0 is rejected. From the result of the research, can be concluded that there is effect of using learning model Think Talk Write assisted mysterious card towards learning with the theme of my hero at the fourth grade students of SD Negeri Batursari 6.